Electoral reforms in India: current discourses - Kumar, B. Venkatesh (Jaipur, 2009)
Electoral laws in India have many loopholes. Unfortunately, over the years, India's various governments have not been serious in addressing electoral reforms. There certainly have been improvements, with India's Election Commission taking some major initiatives in bringing about changes, such as the introduction of electronic voting machines and providing every voter with a voter identity card. But larger issues merit serious attention. It is time that proactive steps are taken by the government so that the people not only get a chance to vote, but also get to vote for the right people who will represent them. This book analyzes and charts the possibilities for electoral reform. It scrutinizes the validity of various recent discourses on electoral reforms and establishes, on the one hand, a dialectical re(-)visioning of the institution of the Election Commission and the process through which it validates existence, and on the other, striving to link aspects of the Commission, the office of the Chief Election Commissioner, and electoral reforms. Along with recommend solutions, the book cites examples from countries such as Germany, Japan, and China.
Keywords: Electoral reforms-India